2002
DOI: 10.1103/physrevb.65.075317
|View full text |Cite
|
Sign up to set email alerts
|

Counting statistics for entangled electrons

Abstract: The counting statistics (CS) for charges passing through a coherent conductor is the most general quantity that characterizes electronic transport. CS not only depends on the transport properties of the conductor but also depends on the correlations among particles which compose the incident beam. In this paper we present general results for the CS of entangled electron pairs traversing a beam splitter and we show that the probability that Q charges have passed is not binomial, as in the uncorrelated case, but… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 22 publications
3
83
0
Order By: Relevance
“…For α = 0 and α = 1 at T B = 1 the third cumulant is zero for every angle both for entangled and for mixed states (the probability distribution of the current is symmetric for those parameters as was previously noted in the α = 0 case in Ref. [21] Fig. 4 as a function of the transmission between left and right arms T B (where simple backscattering has been considered).…”
Section: Higher Order Cumulantsmentioning
confidence: 88%
See 1 more Smart Citation
“…For α = 0 and α = 1 at T B = 1 the third cumulant is zero for every angle both for entangled and for mixed states (the probability distribution of the current is symmetric for those parameters as was previously noted in the α = 0 case in Ref. [21] Fig. 4 as a function of the transmission between left and right arms T B (where simple backscattering has been considered).…”
Section: Higher Order Cumulantsmentioning
confidence: 88%
“…It relied on the use of the mentioned Pauli blocking mechanism in a perfect four-arm beam splitter supplemented by the bunching (antibunching) behavior expected for symmetric (antisymmetric) spatial two-electron wavefunctions. This was done through the analysis of current noise [19], cross-correlators [20], and full counting statistics (FCS) [21]. It was also shown that it is possible to distinguish between different incoming entangled states [20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Bunching (enhanced) and antibunching (suppressed) behavior in the shot noise were predicted for spin singlet and triplet entangled states, respectively [3]. The role of entanglement was later analyzed in the whole probability distribution of the current fluctuations (being the noise power only its second moment) [4]. Further analysis were subsequently performed in the presence of spin-orbit coupling [5], and for states generated in an Andreev double-dot entangler [6].…”
mentioning
confidence: 99%
“…Previous works have proposed to detect the entanglement present in the spin degrees of freedom of a Cooper pair via correlation measurements. 29,[34][35][36][37][38][39][40][41][42][43] The Franson interferometer we consider here, on the other hand, is suited for probing the coherence properties of the spatial degrees of freedom of the emitted Cooper pair. By looking at the interference fringes in the coincidence counts at the output ports, varying the relevant parameters of the Franson interferometer, we can measure the pair correlation length of the emitted Cooper pair, which is proportional to Pippard's length characterizing the extension of the Cooper pair in the superconducting source, as well as the momentum of the center-of-mass motion of the emitted Cooper pair, i.e., the de Broglie wavelength of the emitted Cooper pair as a single object.…”
Section: 33mentioning
confidence: 99%